Cultural Acculluration in Sunda Translation Raudhatul Irfan Fi Ma'rifati Al-Qur'an - Dewi Kuraesin; Dade Mahzuni; Lina Meilinawati Rahayu (Budapest International Research and Critics University, 2022)
There are several points that need to be considered regarding cultural acculturation including, what elements are accepted, what elements are not acceptable, what channels are used, through what institutions, and why they can be accepted. Of course, these points relate to the acculturation of Sundanese culture and Islamic teachings, especially in the Sundanese. Regarding the elements that can be accepted by Islamic teachings into Sundanese culture, namely Islamic teachings are not much different from the character of Sundanese culture at the time of its initial spread. Meanwhile, elements that cannot be accepted in acculturating Sundanese culture and Islamic teachings, especially in terms of creed. Regarding the channels used in acculturating Sundanese culture and Islamic teachings in the Sundanese, it has been going on since the kingdoms of Cirebon and Banten began exploring remote areas in West Java.KH Ahmad Sanoesi who succeeded in acculturating Sundanese culture and spreading religious ideas in Sundanese land, especially in Sukabumi through his Islamic boarding school educational institutions.Thus the acculturation of Sundanese culture and Islamic teachings became the main factor in the ease with which Islamic teachings spread to Sundanese society. The supporting theory in this research is Islamicate from Marshall G Hodgshon's statement and Vernacularization by Anthony H Johns. Thus, that there is a statement